Analisis Pembelajaran Inklusi bagi Anak Berkebutuhan Khusus di SDN 3 Balaraja - Nurfadhillah, Septy; Purwanti, Karunia Nurullita; Puspitasari, Puspitasari; Silfia, Silfia (TSAQOFAH, 2022)
Inclusive education is an education or school that accepts all children regardless of their potential, physical, mental, emotional, social, religious, gender and economic background, but is a system that adapts to the needs of children, both normal and with special needs. The purpose of inclusive education is to encourage the realization of the participation of persons with disabilities or children with special needs in the life of society, nation and state. To achieve the goal, the method used is a descriptive method with a qualitative approach. The sample of this research is the inclusion school of SDN 3 Balaraja. The instruments used are observation, interview guidelines and documentation. Based on the data analysis carried out, the following research results showed that the learning process that was applied did not differentiate between ABK students and regular students, only that the teacher was always focused on ABK students. because every ABK student needs special attention. The material and learning system are relatively the same as regular students, so there is no difference between ABK students and regular students. It's just that before carrying out the learning process in the classroom, schools have certain indicators such as identifying students with special needs. In the implementation of learning, a lesson plan is needed that distinguishes the RPP for regular children from children with special needs, namely the indicator of achievement. For example, students are able to read, while children with special needs are changed to children who are able to say letters.